2014
DOI: 10.1016/j.ajic.2014.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes of infections caused by extremely drug-resistant gram-negative bacilli in patients hospitalized in intensive care units

Abstract: Background Extremely drug-resistant gram-negative bacilli (XDR-GNB) increasingly cause healthcare-associated infections (HAIs) in intensive care units (ICUs). Methods A matched case-control (1:2) study was conducted from February 2007 to January 2010 in 16 ICUs. Case and control subjects had HAIs caused by GNB susceptible to ≤1 antibiotic versus ≥2 antibiotics, respectively. Logistic and Cox proportional hazards regression assessed risk factors for HAIs and predictors of mortality, respectively. Results Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 36 publications
(36 reference statements)
2
39
0
1
Order By: Relevance
“…Many studies have so far failed to demonstrate a clear relationship between antimicrobial resistance and mortality. 8,10,11,27 A possible explanation is that the currently used definitions for MDR bacteria may not be directly applicable in clinical care, because they do not take into account infection type, age, or risk adjustment. 13 The other factor independently associated with mortality was type of infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have so far failed to demonstrate a clear relationship between antimicrobial resistance and mortality. 8,10,11,27 A possible explanation is that the currently used definitions for MDR bacteria may not be directly applicable in clinical care, because they do not take into account infection type, age, or risk adjustment. 13 The other factor independently associated with mortality was type of infection.…”
Section: Discussionmentioning
confidence: 99%
“…There is no clear independent correlation between antimicrobial resistance and patients' mortality. [8][9][10][11] Clarifying the relationship between patient risk factors and pediatric HAI mortality could allow improved targeting of interventions on the patients most at risk of adverse outcome. The aims of this study were to describe trends in the epidemiology of HAIs in Italian and Brazilian pediatric ICUs over a 5-year period and to evaluate patient risk factors and the clinical impact of MDR-HAI in children admitted to ICUs.…”
mentioning
confidence: 99%
“…A matched case-control study (1:2) in hospitals in New York City, including both pediatric and adult oncology patients in intensive care between February 2007 and January 2010, found that immunocompromised state (OR, 1.55; P 5 .047) and exposure to amikacin (OR, 13.81; P < .001), levofloxacin (OR, 2.05; P 5 .005), or trimethoprim-sulfamethoxazole (OR, 3.42; P 5 .009) were factors associated with XDR gram-negative bacilli health care-associated infections. 79 A retrospective chart review of 192 adults with cancer in China who had Enterobacter bacteremia evaluated risk factors and treatment outcomes associated with extended-spectrum cephalosporin resistance. Recent use of a third-generation cephalosporins, older age, tumor progression at last evaluation, recent surgery, and nosocomial acquisition were all associated with extended spectrum cephalosporin resistant Enterobacter bacteremia.…”
Section: Risks For Multidrug-resistant Organisms In the Febrile Neutrmentioning
confidence: 99%
“…This change may be accompanied by a more fearful spectre; that of antibiotic resistance. Multi-drug resistant Gram-negative bacteraemia is already leading to increasing therapeutic challenges in the ICU 6 and is being reported in patients with cirrhosis. 7 Sepsis is likely to remain a major problem in cirrhosis and we need to consider strategies other than simply giving more or different antibiotics.…”
Section: Acknowledgementmentioning
confidence: 99%
“…5 We believe that this is probably due to combination of under-reporting of these nosocomial infections by the respective hospitals and coding error since the 'no-pay rule' to claim additional payments for treating Hospital In-patient Infections from Centers for Medicare and Medicaid services was passed only in 2008. 6 Infections in cirrhotics will continue to be a major problem. Studies are urgently needed to develop strate-…”
mentioning
confidence: 99%